Evaluation of Impact of Low Hb, MCV, MCHC and MCH on Cognitive Ability of Undergraduated Medical Students - Abdali, Ashraf; Amal, Maghferatullah; Shamalwal, Sayed Rahim Shah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Introduction: Low concentrations of hemoglobin or anemia can contribute chronic brain hypoxia and reduced aerobic capacity, thus increasing the risk of dementia or cognitive decline. From the clinical point of view, brain ischemia is a known risk factor of cognitive dysfunction and dementia. We investigated correlation and impact of low Hb, MCV, MCHC and MCH on cognitive abilities from 386 participants on 59 top 10 undergraduate medical students. Objective: This study aimed to determine and evaluate the correlation and impact of low Hb, MCV, MCHC and MCH on cognitive abilities of 59 top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province of Afghanistan. Method and Materials: It is prospective descriptive cross sectional study, on 59 top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province from 2023/ Oct / 12 to 2023/ Nov / 02. The including parameters were Hb, MCV, MCHC and MCH of all 386 participants under study that recorded in computer special format. Hb, MCV, MCHC and MCH are done by special regents and micro lab. Recorded findings processing, comparison and evaluation results have been identified by IBM SPSS-23 version. Results: The study was conducted during (20) days on 386 undergraduated medical students in Ahmad shah Abdali Higher Education Institute of Khost province. Initially we described all male participants according to age. At the current study all male participants were with (mean age: 23.14 ± 3.68; range: 20-45 years). All participants of this study were from all (1st, 2nd, 3rd, 4th, 5th and 6th) classes. Statistic description of all participants, according to Hb, MCV, MCHC and MCH shows that normal range of Hb level for male (14-16.6g/dl) was more prevalent 301(77.97). Low level of Hb for male (Low ˂ 13.5g/dl) was 19(4.92) and high level of Hb for male (High > 16.6g/dl) was 66(17.09).The normal range of MCV (80-95%) was 327(84.71), low range (Low ˂80) was 54(13.98) and high range (High>95%) was 5(1.29).The normal range of MCHC (32-36%) was 370(95.85), low range (Low ˂ 32) was 15(3.88) and high range (High>36%) was 1(0.25).The normal range of MCH (23-31%) was 322(83.41), low range (Low ˂ 23) was 19(4.92) and high range (High>31%) was 5(11.65). In the second part of this study we described all above parameters in the group of all 59 top 10 participants students for comparative outcomes. Statistic description of 59 top 10 participants, according to Age, Hb, MCV, MCHC and MCH shows that at the current study top 10 participants were with (mean age 23.40± 2.78; range: 18-32 years). Normal range of Hb level for male (14-16.6g/dl) was 43(72.88). Low level of Hb for male (Low ˂ 13.5g/dl) was 2(3.38) and high level of Hb for male (High > 16.6g/dl) was 14(23.72). The normal range of MCV (80-95%) was 51(86.44), low range (Low ˂80) was 8(13.55) and high range (High>95%) was 0(0). The normal range of MCHC (32-36%) was 57(96.61), low range (Low ˂ 32) was 2(3.38) and high range (High>36%) was 0(0).The normal range of MCH (23-31%) was 50(84.74), low range (Low ˂ 23) was 2(3.38) and high range (High>31%) was 7(11.86).Pearson correlation between Hb and MCV is at the 0.01 level significant, (P<0.00). Conclusion: Overall, findings of our study indicated that, low Hb, MCV, MCHC and MCH have significant correlation with cognitive ability of undergraduated students. However, this issue needs to further investigations to confirm these findings.